PENENTUAN SIFAT MEKANIS SERAT SABUT KELAPA - Bakri, Bakri (Jurnal MEKANIKAL, 2010)
Coir fibres are obtained from coconut husk.  In application of composite materials, coir fibres  are  influenced  by  mechanial  properties.    This  study  aims  to  characterize  the mechanical properties of coir fibres. To characterize mechanial properties of coir fibres, variation of gauge length of fibres was conducted. The result showed that variability of cross  setional  areas  influenced  mechanical  properies  and  that  the  Young’s  modulus, breaking stress and breaking strain can be determined.